MEASURING EFFICIENCY AND EFFECTIVENESS OF INDONESIAN REGIONAL DEVELOPMENT BANKS - Akbar, Bahrullah; Djazuli, Achmad; Jariyatna, Jariyatna (Badan Pemeriksa Keuangan Republik Indonesia, 2019)
This study explores the efficiency and effectiveness of Regional Development Banks (BPD) based on the results of performance audit conducted by the Audit Board of the Republic of Indonesia (BPK RI). Performance audit produces conclusion and recommendation on economy, efficiency and effectiveness (3E). BPDs are expected to be regional champions in their respective regions. Data envelopment analysis (DEA) is used to calculate the level of production and operational efficiency of the BPDs while the level of effectiveness is assessed based on the results of performance audit conducted by BPK RI. The results show that both efficiency and effectiveness are not always achieved. This study also identifies BPD that have the highest value of production and operational efficiency and the level of effectiveness. The BPD obtained the highest efficiency and effectiveness values that could be used as a reference for other BPDs to make improvements and become a regional champion in their respective regions.